2017
DOI: 10.1103/physrevb.95.224411
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic exchange in LiCu2O2

Abstract: We investigate the magnetic properties of the multiferroic quantum-spin system LiCu2O2 by electron spin resonance (ESR) measurements at X-and Q-band frequencies in a wide temperature range (TN1 ≤ T ≤ 300 K). The observed anisotropies of the g tensor and the ESR linewidth in untwinned single crystals result from the crystal-electric field and from local exchange geometries acting on the magnetic Cu 2+ ions in the zigzag-ladder like structure of LiCu2O2. Supported by a microscopic analysis of the exchange paths … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In our numerical study with couplings J 1 = 1, J 2 = −0.6, D = 0.3, this was indeed the case for the scar state in the sector k = 0, S z Tot = 0, g = 1. We note that the "CuO 2 ribbon chain" materials [87][88][89][90]92] have the desired opposite signs of J 1 and J 2 .…”
Section: Application: Reduction To New Spin-1/2 Models With a Magnon mentioning
confidence: 81%
See 1 more Smart Citation
“…In our numerical study with couplings J 1 = 1, J 2 = −0.6, D = 0.3, this was indeed the case for the scar state in the sector k = 0, S z Tot = 0, g = 1. We note that the "CuO 2 ribbon chain" materials [87][88][89][90]92] have the desired opposite signs of J 1 and J 2 .…”
Section: Application: Reduction To New Spin-1/2 Models With a Magnon mentioning
confidence: 81%
“…This model has been considered in the context of the magnetoelectric effect in ferroelectric materials [84][85][86] and is believed to describe materials such as LiCuVO 4 [87,88] and LiCu 2 O 2 [89,90]. The DM interaction breaks the spin-SU(2) symmetry, and the presence of this multiplet is a nontrivial "scar" property.…”
Section: Application: Reduction To New Spin-1/2 Models With a Magnon mentioning
confidence: 99%
“…The ESR spectrum consists of a single exchange-narrowed Lorentz line with a g-tensor given by g c = 2.28 and g a = g b = 2.05. Angular dependent ESR measurements revealed a significant anisotropy of the line width in the paramagnetic regime [99] as depicted in figure 8. Supported by a microscopic analysis of the exchange paths involved, it was shown that the symmetric anisotropic exchange contributions from NN inter-chain interaction J 1 (inset in the middle frame of figure 8) and NN intra-chain interaction J 2 (cf leading contribution in LiCuVO 4 , inset in the left frame) are not sufficient to explain the observed anisotropy with the prominent maximum of the line width for the magnetic field aligned along the a-axis.…”
Section: The Zig-zag Ladder Licu 2 Omentioning
confidence: 92%
“…The study of quantum phase transitions in low dimensional spin systems has been a Frontier area of research due to abundance of effective low-dimensional magnetic materials [1][2][3][4][5][6][7][8][9][10] which exhibits a zoo of phases [11][12][13][14][15][16][17][18][19][20][21][22][23]. The confinement and interplay of exchange interactions in low dimensional systems like spin chains [6,24,25], spin ladders [2,3,26,27] or two dimensional systems [28,29] can give rise to various interesting ground state (GS) properties [14,[30][31][32][33][34][35]. Recently syn-thesized materials show that many of these spin-1/2 systems are frustrated even in one dimension (1D) [7][8][9][10], whereas the low dimensional systems can be either geometrically frustrated i.e.…”
Section: Introductionmentioning
confidence: 99%